The overall computer/mobile devices usage time is related to newly diagnosed non-alcoholic fatty liver disease: a population-based study. (2nd October 2016) - Meng, Ge; Liu, Fangfang; Fang, Liyun; Li, Chunlei; Zhang, Qing; Liu, Li; Wu, Hongmei; Du, Huanmin; Shi, Hongbin; Xia, Yang; Guo, Xiaoyan; Liu, Xing; et al.
Abstract: Background: The computer/mobile devices usage time (CMD-UT) is closely related to a sedentary lifestyle, which is an important risk factor for non-alcoholic fatty liver disease (NAFLD). But their direct relationship remains unclear. Aims: We aimed to examine the relationship between CMD-UT and newly diagnosed non-alcoholic fatty liver disease (NAFLD) in Chinese adults. Methods: This cross-sectional study was conducted on 7516 adults in Tianjin, China. The CMD-UT was collected via a questionnaire included five categories. NAFLD [with normal or elevated alanine transaminase (ALT) levels] was diagnosed by at least twice liver ultrasonography examinations and serum ALT concentrations (>41 U/L in males and >33 U/L in females). Results: The prevalence of overall NAFLD, NAFLD with normal or elevated ALT levels was 18.2, 14.2, and 4.0%, respectively. After adjustments for potential confounding factors, the odds ratios (95% confidence interval) of having overall NAFLD by increasing CMD-UT levels were 1.00 for <1 h/d, 1.58 (1.22–2.05) for 1-3 h/d, 1.58 (1.18-2.11) for 3–5 h/d, 1.65 (1.21-2.27) for 5–10 h/d, and 1.99 (1.29-3.05) for ≥10h/d ( P -trend for CMD-UT levels = 0.02), respectively. Similar relations were observed with the use of NAFLD with normal or elevated ALT levels. Conclusions: The present study is the first to find that CMD-UT levels are independently associated with NAFLD. Key Messages: The computer/mobile devices usage time levels are independently associated with the prevalence of non-alcoholic fatty liver disease.